FAKTOR YANG MEMPENGARUHI MANAJEMEN KEBERSIHAN MENSTRUASI PADA REMAJA PUTRI DI SMPN1 GUNUNG MERIAH KABUPATEN ACEH SINGKIL - Ema Mahrani; Thomson P Nadapdap; Mey Elisa Safitri (Poltekkes Kemenkes Medan, 2023)
Menstrual Hygiene Management is the management of hygiene and health when a woman is menstruating, poor management of menstrual hygiene can cause health problems such as reproductive tract infections, urinary tract infections and an increased risk of cervical cancer. This study aims to determine the affecting factors on menstrual hygiene management in female studetnts at SMPN 1 Gunung Meriah, Aceh Singkil Regency. This is a quantitative study with a cross sectional approach. The population in this study was female students at SMPN 1 Gunung Meriah as many as 302 students, and the sample 75 students. Data analysis used Chi-square test and Multiple Logistic Regressions. The results showed that the factors influencing management of menstrual hygiene in female students of the School were knowledge (p=0.002), mother support (p=0.000), friend support (p=0.001) and facilities and infrastructure (p=0.001). 0.030), while the unrelated factors were attitude (p=0.662) and teacher support (p=0.088). The most dominant factor affecting menstrual hygiene management was mother's support with a value of Exp(B)/OR = 8,329